2010
DOI: 10.1002/jcu.20662
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of real‐time 3D sonography in the diagnosis of congenital Mullerian anomalies in high‐risk patients with respect to the phase of the menstrual cycle

Abstract: Real-time 3DUS is an accurate method that can be used for the diagnosis of congenital mullerian defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 19 publications
0
19
0
2
Order By: Relevance
“…Multiple studies have compared 3D sonography to other imaging modalities and surgical findings, and the studies have shown that 3D sonography is better than 2D sonography, 6 8 hysterosalpingography, 9 , 10 and hysteroscopy 11 , 12 and equivalent to MRI in diagnostic accuracy for müllerian anomalies 7 , 11 , 13 . These comparisons hold true for all 7 classes of uterine malformations.…”
Section: Three‐dimensional Sonography For Uterine Anomaliesmentioning
confidence: 97%
“…Multiple studies have compared 3D sonography to other imaging modalities and surgical findings, and the studies have shown that 3D sonography is better than 2D sonography, 6 8 hysterosalpingography, 9 , 10 and hysteroscopy 11 , 12 and equivalent to MRI in diagnostic accuracy for müllerian anomalies 7 , 11 , 13 . These comparisons hold true for all 7 classes of uterine malformations.…”
Section: Three‐dimensional Sonography For Uterine Anomaliesmentioning
confidence: 97%
“…Fifty-four subjects (19 %) were diagnosed with a uterine anomaly, and 3DUS correctly identifi ed 52 (92.3 %) of the anomalies; two partial septate uteri were misclassifi ed as bicornuate and arcuate. When 3DUS and 2DUS were compared for the diagnosis of uterine anomalies during different phases of the menstrual cycle, both modalities had higher sensitivity and specifi city during the luteal phase, but 3DUS demonstrated greater sensitivity and specifi city in both the follicular and luteal phases, and the diagnostic accuracy of 3DUS was comparable to HSG, hysteroscopy, and laparoscopy [ 52 ]. Lastly, the reproducibility of the interpretation of 3DUS volumes to diagnose uterine anomalies has been established [ 61 ].…”
Section: Three-dimensional Ultrasonographymentioning
confidence: 96%
“…Hazánk-ban nem terjedt el ilyen célra, de külföldön a diagnosztikus műtétek kiváltására egyre szélesebb körben használják az MRI-t, mivel a nem invazív eljárások közül a legnagyobb szenzitivitással rendelkezik és költséghatékonyabb eljárás, mint a műtétes megoldás [29]. Az utóbbi időben egyre több szerző felveti a 3D ultrahangvizsgálat hasznosságát, mivel pontossága megfelelő és a 2D ultrahangfelvételeknél jóval megbízhatóbb a méhűri eltérések kimutatásában, illetve az MRI-hez hasonlóan az uterus külső felszínének megítélésére is alkalmas, de annál egyszerűbb és olcsóbb eljárás [30,31]. Diagnosztikai célból alkalmazható még a hysterosalpingographia és a hysterosalpingo-sonographia is.…”
Section: Eredeti Közleményunclassified